A new species of Geogamasus Lee (Mesostigmata: Ologamasidae), with morphological details on species of the genus - Barros, Avyla R.A. [UNESP]; De Azevedo, Emiliano B. [UNESP]; Silva, Edmilson S.; De Moraes, Gilberto J.; Castilho, Raphael C. [UNESP] (Systematic and Applied Acarology Society, 2021)
Geogamasus lasaroi Barros, Azevedo & Castilho sp. nov. is described based on the morphology of adult females collected from soil-litter of a well preserved fragment of the natural vegetation of the Caatinga biome, in Alagoas state, northeastern Brazil. In addition, key information on the morphology of the world Geogamasusspecies is presented in a tabular format.
Keywords: predatory mites; Rhodacaroidea; soil mites; taxonomy